The end of early music: A period performer's history of music for the twenty-first century - Haynes, Bruce 1942-2011 (New York Oxford university press, 2007)
Part history, part explanation of early music, this book also plays devil's advocate, criticizing current practices and urging experimentation. Haynes, a veteran of the movement, describes a vision of the future that involves improvisation, rhetorical expression, and composition. Written for musicians and non-musicians alike.